The Aesthetics Of The Sardine - Simone Hélène Sirven (The Journal of Studies in Language, Culture and Society)
Using the figure of the sardine, the article explores the issues at stake in contemporary art and the digital world, the internet, in relation to current post-colonial situations and contexts. Some significant works by contemporary artists (Sedira, Fatmi, Abdessemed, Scurti) contribute to the symbolism and aesthetics of the sardine, as do the traditions and economy of this famous fish.